2015
DOI: 10.1093/mnras/stv2677
|View full text |Cite
|
Sign up to set email alerts
|

Extreme value statistics of weak lensing shear peak counts

Abstract: The statistics of peaks in weak gravitational lensing maps is a promising technique to constrain cosmological parameters in present and future surveys. Here we investigate its power when using general extreme value statistics which is very sensitive to the exponential tail of the halo mass function. To this end, we use an analytic method to quantify the number of weak lensing peaks caused by galaxy clusters, large-scale structures and observational noise. Doing so, we further improve the method in the regime o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Extreme value statistics allow us to assess the probability of finding unusual objects in the Universe (e.g. Davis et al 2011;Waizmann et al 2011;Yaryura et al 2011;Reischke et al 2016). Since we did not find a halo in the MXXL simulation with a distribution of substructure like that seen in Abell 2744, we can use extreme value theory to estimate the simulation volume that would be needed to find at least one halo with the same substructure.…”
Section: Extreme Value Statisticsmentioning
confidence: 99%
“…Extreme value statistics allow us to assess the probability of finding unusual objects in the Universe (e.g. Davis et al 2011;Waizmann et al 2011;Yaryura et al 2011;Reischke et al 2016). Since we did not find a halo in the MXXL simulation with a distribution of substructure like that seen in Abell 2744, we can use extreme value theory to estimate the simulation volume that would be needed to find at least one halo with the same substructure.…”
Section: Extreme Value Statisticsmentioning
confidence: 99%
“…Using a Bayesian approach with flat priors Ω m ∈ [0, 0.7] and σ 8 ∈ [0.4, 1.4] the probability of measuringd meas. if the true parameters are π, is then proportional to 13) where N d is the length of the vectord meas. andΣ −1 is the inverse of our covariance estimate.…”
Section: Likelihood Analysismentioning
confidence: 99%
“…Pires et al (2012) demonstrated that peak counts are the best statistic to break the σ 8 -Ω m degeneracy among the second-order weak lensing statistics. Reischke et al (2016) have suggested that the extreme value statistic of peak counts can tighten even more the constraints on cosmological parameters.…”
Section: Introductionmentioning
confidence: 99%